2015
DOI: 10.1371/journal.pgen.1005153
|View full text |Cite
|
Sign up to set email alerts
|

A Stress-Induced Small RNA Modulates Alpha-Rhizobial Cell Cycle Progression

Abstract: Mechanisms adjusting replication initiation and cell cycle progression in response to environmental conditions are crucial for microbial survival. Functional characterization of the trans-encoded small non-coding RNA (trans-sRNA) EcpR1 in the plant-symbiotic alpha-proteobacterium Sinorhizobium meliloti revealed a role of this class of riboregulators in modulation of cell cycle regulation. EcpR1 is broadly conserved in at least five families of the Rhizobiales and is predicted to form a stable structure with tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(84 citation statements)
references
References 88 publications
1
83
0
Order By: Relevance
“…DNA fragments encompassing the native 5´‐UTR uncovered by previous RNAseq experiments (Schlüter et al ., ) and a short part of the coding region of each mRNA (15 codons of SMb20442 and 12 of SMc03121) were translationally fused to egfp under the control of the constitutive P syn promoter in plasmid pR_EGFP. Each reporter construct was mobilized to a S. meliloti SinR/SinI/ExpR‐less strain harbouring either pSKControl + or pSKNfeR1 + , which express the control SmelC812 RNA or NfeR1, respectively, from the SinR‐dependent P sinI promoter upon induction of sinR transcription (cloned in these plasmids downstream of P lac ) with IPTG (Robledo et al ., ). NfeR1‐mediated regulation of the target mRNAs was then assessed by fluorescence measurements of IPTG induced and uninduced stationary TY cultures of each reporter strain, i.e.…”
Section: Resultsmentioning
confidence: 97%
“…DNA fragments encompassing the native 5´‐UTR uncovered by previous RNAseq experiments (Schlüter et al ., ) and a short part of the coding region of each mRNA (15 codons of SMb20442 and 12 of SMc03121) were translationally fused to egfp under the control of the constitutive P syn promoter in plasmid pR_EGFP. Each reporter construct was mobilized to a S. meliloti SinR/SinI/ExpR‐less strain harbouring either pSKControl + or pSKNfeR1 + , which express the control SmelC812 RNA or NfeR1, respectively, from the SinR‐dependent P sinI promoter upon induction of sinR transcription (cloned in these plasmids downstream of P lac ) with IPTG (Robledo et al ., ). NfeR1‐mediated regulation of the target mRNAs was then assessed by fluorescence measurements of IPTG induced and uninduced stationary TY cultures of each reporter strain, i.e.…”
Section: Resultsmentioning
confidence: 97%
“…MmgR, MmgR Δ33-51 , the Hfq-independent asRNA812, or the Hfq-dependent Sm84 (17,27) sRNA was induced in the mmgR Δ33-51 background by an isopropyl-␤-D-thiogalactopyranoside (IPTG)-inducible plasmid expression system based on the sinR-sinI regulation that has been previously introduced elsewhere (see Fig. S1 in the supplemental material) (30,57). In brief, a PCR-generated DNA fragment with the complete sequence of the S. meliloti 2011 sinR gene followed by the sinR-sinI inter-open reading frame (ORF) region was fused to a PCR-amplified DNA fragment containing the sequence of MmgR, MmgR Δ33-51 , or Sm84.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, S. meliloti expresses a functional homolog of the Escherichia coli Hfq protein, a chaperone of RNA-RNA interactions and a modulator of RNA activity (22)(23)(24)(25)(26)(27)(28)(29). Nevertheless, the biological implications of the large S. meliloti RNome remain largely unexplored (20), since only four small RNAs have been functionally characterized so far, i.e., the cell cycle regulator sRNA EcpR1 (30), the quorumsensing regulator sRNA RcsR1 (31), and the tandemly encoded orthologs AbcR1 and AbcR2 (32). We are tempted to speculate that the large regulatory network is yet to be revealed.…”
mentioning
confidence: 99%
“…73 Recently, Robledo et al 74 have reported a riboregulator with a role in the regulation of cell cycle progression. It is induced under the conditions of a cytoprotective and adaptive response.…”
Section: Engineering and Characterization Of Stress-inducible Ribormentioning
confidence: 99%